PENDIDIKAN AKHLAK MENURUT IMAM HASAN AL-BANNA DALAM KITAB MAJMUATU RASA’IL - choli, Ifham; Farhana (Journal of Islamic Education Studies, 2022)
important issue, so that every aspect of the Islamic education process always fosters noble character. Morals are traits that have been embedded in the soul that encourage one's behavior easily so that it becomes habitual behavior. This study uses the type of research in the form of Library Research (Library Research). Library research is a research conducted by reading, studying books by quoting from various theories and opinions that have a relationship with the problem under study. This study takes the thinking of Imam Hasan Al-Banna because Imam Hasan has a character of its own renewal that distinguishes it from the previous scholars. Among the most important aspects of education in the Ta'lim Treatise is the moral aspect. Among the most important aspects of education in the Ta'lim Treatise is the moral aspect. Hasan al Banna called it the "stick of command for change", because morality according to Al Banna is the first pillar of societal change. Al Banna said that Islam depends on changing the affairs of this ummah on changes in morals and cleanliness of the soul. The purpose of education according to Hasan Al Banna is oriented to the realization of Islamic identity, namely forming a Muslim personality.